Estimating the Impact and Cost of the WHO 2010 Recommendations for Antiretroviral Therapy - John Stover; Lori Bollinger; Carlos Avila (AIDS Research and Treatment)
In July 2010, WHO published new recommendations on providing antiretroviral therapy to adults and adolescents, including starting ART earlier, usually at a CD4 count of 350 or lower, specific regimens for first- and second-line therapies, and other recommendations. This paper estimates the potential impact and cost of the revised guidelines by first, calculating the number of people that would be in need of antiretroviral therapy (ART) with different eligibility criteria, and second, calculating the costs associated with the potential impact. Results indicate that switching the eligibility criterion from CD4 count <200 to <350 increases the need for ART in low- and middle-income countries (country-level) by 50% (range 34% to 70%). The costs of ART programs only to increase coverage to 80% by 2015 would be 44% more (range 29% to 63%) when switching the eligibility criterion to CD4 count <350. When testing and outreach costs are included, total costs increase by 62%, from US$26.3 billion under the previous eligibility criterion of treating those with CD4 <200 to US$42.5 billion using the revised eligibility criterion of treating those with CD4 <350.